Ijtihadi Models in Fiqh Studies - Sufriadi Sufriadi; Ibnu Mukti; Mahmudi Mahmudi; Nurazizah Nurazizah (Budapest International Research and Critics University, 2021)
This study was conducted to find models of ijtihad in the study of fiqh. The active role of Islamic scholars in providing legal answers to actual problems is a necessity and cannot be avoided. Various legal references have been contained in various fiqh books by previous scholars, but from another point of view it must also be realized that the formulation of Islamic law contained in the fiqh books left by the fuqaha has in some aspects lost its transformational ability. From that, the actualization of the texts of the fiqh books is one of the efforts to solve problems for those who do not leave the fiqh books.This research is in the form of literature research with qualitative research type, which emphasizes inductive analysis of thought processes related to the dynamics of the relationship between observed phenomena and uses scientific logic. A content analysis approach can involve a type of analysis, in which communications are categorized and classified. The stage of interpreting the data that has been found in accordance with the focus of the object of study to find relevance, correlation, sometimes even being able to offer and reconstruct new thoughts from the data that has been found. The results of the study found hIslamic law consists of two parts, Islamic law in the form of teachings contained in the Qur'an and mutawatir hadith produced through qath'i al-dilalah. Legal construction is carried out by a person who has the capacity of a mujtahid by using al-qawaid al-ushuliyah in interpreting the text of the Qur'an and hadith to find laws for new problems. The models or patterns of ijtihad used by previous and contemporary scholars include; Ijtihad Intiqa'i, Insha`i and Qiyas.